Diversity of Media and Learning Methods in History Learning 2013 Curriculum at Three Public High Schools in Brebes Regency - Amirudin, Andi; Suryadi, Andy (Indonesian Journal of History Education, 2019)
This study discusses the diversity of media and learning methods in learning the history of Curriculum 2013 in three State High Schools in Brebes District. The research method used a qualitative approach. The techniques used to collect data are interview methods, observation, and documentation. Purposive sampling is also used. Technique of data validity with source triangulation and Technique. Data analysis with interaction analysis. The results showed that only two SMA Negeri utilize the learning media with the maximum and by the Curriculum 2013, which prioritizes the development of technology and information as a medium of learning is SMA Negeri 1 Brebes and SMA Negeri 1 Larangan while SMA Negeri 2 Brebes less use of learning media maximally. In addition, the use of media is widely used by students rather than teachers. The learning media used in SMA Negeri 1 Brebes, SMA Negeri 2 Brebes, and SMA Negeri 1 Larangan are LCD projector, sound system, computer/laptop, PowerPoint, video learning, pictures/photos, student books, teacher books, worksheets, maps, and the Internet. The methods include lectures, discussions, snowball throwing, and presentations.